DELIVERY OF ANTI-PD-1 GENE WITH RECOMBINANT ADENO-ASSOCIATED VIRUS (RAAV) AS PREVENTIVE AND CURATIVE THERAPY OF INFECTIOUS DISEASES IN CHILDHOOD : LITERATURE REVIEW - Farros Yuftariq Izzad Afla; Arifa Mustika; Muhammad Arsy Reza Suyudi; Zumara Ma'rifah Azzahra (Universitas Airlangga, 2022)
Infections in children are common and are the highest cause of hospitalization in children, especially in children aged 0-4 years. The binding of PD-1 (Programmed Cell Death-1) glycoprotein on its ligand in CD4+ and CD8+ T cells activates a pathway that results in T cell dysfunction. Inserting the anti-PD1 gene into rAAV opens opportunities for preventing and treating infections in children. This literature review aims to determine the potential of anti-PD1 gene rAAV as a new modality for preventing and treating pathogen infections in children. The procedure of searching for literature to answer questions was carried out through online searching of journals in the last ten years. The use of anti-PD-1 has shown to increase the immune response against certain viral, bacterial and parasitic infections. Using rAAV as an anti-PD-1 gene vector has great potential to be a preventive or curative therapy for various infections in children. Further research and development are needed to determine the viral model, dose, indications, and contraindications to the use of the rAAV-transmitted anti-PD-1 gene for the treatment of infectious diseases in children.